2021
DOI: 10.3390/ani11020518
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fasting on the Spexin System in Broiler Chickens

Abstract: Spexin (SPX) is a highly conservative peptide hormone containing 14 amino acids and was discovered in 2007 by bioinformatics methods. However, nothing is yet known about its role in the metabolism of birds, including broilers. The aim of this study was to investigate the effect of short-term fasting (2, 4, and 8 h) on the concentration of SPX in blood serum and the expression levels of the genes encoding this peptide (SPX1) and its receptors, GALR2 and GALR3, in the tissues involved in carbohydrate and lipid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…During the differentiation process we showed that the expression of GalR2 decreased while the expression of GalR3 increased. Many earlier studies have confirmed that SPX is widely expressed in many tissues of mammals, birds and other groups of animals [ 2 , 3 , 25 , 26 ], which indirectly suggests that SPX could play a role in the regulation of the metabolism of different tissues. Studies on the expression of GalR2 and GalR3 receptors in muscle tissue as well as in C2C12 cells have been more limited; however, both mRNA and protein studies indicate that both galanin receptor isoforms are expressed in muscle tissue.…”
Section: Discussionmentioning
confidence: 93%
“…During the differentiation process we showed that the expression of GalR2 decreased while the expression of GalR3 increased. Many earlier studies have confirmed that SPX is widely expressed in many tissues of mammals, birds and other groups of animals [ 2 , 3 , 25 , 26 ], which indirectly suggests that SPX could play a role in the regulation of the metabolism of different tissues. Studies on the expression of GalR2 and GalR3 receptors in muscle tissue as well as in C2C12 cells have been more limited; however, both mRNA and protein studies indicate that both galanin receptor isoforms are expressed in muscle tissue.…”
Section: Discussionmentioning
confidence: 93%
“…This same effect was noted in serum in rats [ 166 ]. Our research performed in broiler chickens also proved that SPX expression is regulated by fasting time in fat tissue, the liver, and muscle, which also indicates that the SPX system could be a potent regulator of carbohydrate and lipid metabolism in birds [ 153 ].…”
Section: Spexinmentioning
confidence: 93%
“…Despite the fact that the research on this peptide is relatively recent, the knowledge about it has systematically increased. Research conducted on many different groups of animals showed a wide expression of this peptide in many different tissues, including fat tissue/adipocytes [ 152 , 153 , 154 , 155 , 156 , 157 , 158 ]. The first study that connected SPX with fat tissue metabolism were experiments performed by Walewski et al in 2014.…”
Section: Spexinmentioning
confidence: 99%
“…25 In chicken broilers, serum SPX began to increase after 2 h fasting and a statistically significant increase was observed after 4 and 8 h. 26 Moreover, after fasting, SPX transcripts were increased in the liver and decreased in adipose tissue and muscle, which are important tissues in the coordination of energy homeostasis. 26…”
Section: Food Intakementioning
confidence: 99%
“…It was also demonstrated that short-term food deprivation (7 days) increased SPX mRNA levels in the hypothalamus, and this returned to baseline levels after refeeding. 25 In chicken broilers, serum SPX began to increase after 2 h fasting and a statistically significant increase was observed after 4 and 8 h. 26 Moreover, after fasting, SPX transcripts were increased in the liver and decreased in adipose tissue and muscle, which are important tissues in the coordination of energy homeostasis. 26 Overall, SPX seems to be an orexigenic factor under negative energy balance.…”
Section: Food Intakementioning
confidence: 99%